Train officers, students for positive interactions. Issue 6 (October 2017) - Miles, David
Abstract : Many days we wake up to the news, and very seldom is the story about the good things police officers have done. I understand that sensationalism is what sells papers or attracts viewers to watch the news. Most stories about the interactions of police with the community show only the situations that go bad.